PEKERJAAN STRUKTUR HIGH RISE BUILDING PADA PROYEK PEMBANGUNAN KANTOR BEST INDUSTRY GROUP - Wirawan Abied Jayawardana (Jurnal Vokasi Teknik Sipil, 2024)
An internship is a set of exercises that students complete as part of training to advance their soft skill competencies. Purposive sampling is used in this study, meaning that the sample is chosen in accordance with predetermined standard that are carefully considered, namely interviews and observations. The project data results obtained included the Best Industry Surabaya Office construction project by PT. Sinar Waringin Adi Perkasa served as structural contractor and PT. Best as the owner or project owner. The Best Industry Surabaya Office Project has a land area of ± 2406 m² with a total of 10 floors (9 floors + 1 roof floor). The project value of the Surabaya Best Industry Office Project is IDR. 9,900,000,000. In this research, the results showed that during the work process in accordance with the RKS, the work drawings used were very clear and easy to understand, the implementation of the K3 system was not implemented well and operational activities ran quite smoothly and well.